2008
DOI: 10.1149/1.2902308
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence from Pulsed-Laser-Deposited (Sr[sub 0.7]Ba[sub 0.3])[sub 2]SiO[sub 4]:Eu[sup 2+] Thin-Film Phosphors

Abstract: Thin-film ͑Sr,Ba͒ 2 SiO 4 :Eu 2+ phosphors were pulsed-laser deposited on quartz glass, sapphire, and Si wafers. The processing conditions were optimized to reduce substrate temperature during deposition and also to avoid high-temperature postdeposition annealing and reduction. In this study, the maximum processing temperature was reduced to 700°C, which must be lowered even further to produce on-chip phosphor films. The exact composition of the film obtained under the optimum processing conditions was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…2b, because in any coordination system a barium ion is larger than a strontium ion by about 20%, which inflated the lattice and led to the peak shift. In particular, our previous structural study based on Rietvelt analysis 16 revealed that the addition of a large amount of barium elongated an axis ͑b-axis for Pmnb symme-try͒, while the others were not altered. When considering four major peaks located in the range 30.5-32°, such as ͑121͒, ͑022͒, ͑200͒, and ͑103͒ peaks, the effect of a large amount of barium, namely, the peak shift toward the small angle side, was only detected for the ͑121͒ and ͑022͒ peaks, while the ͑200͒ and ͑103͒ peaks coincided exactly with the standard data of non-barium-doped and small amounts of barium-doped samples, as shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…2b, because in any coordination system a barium ion is larger than a strontium ion by about 20%, which inflated the lattice and led to the peak shift. In particular, our previous structural study based on Rietvelt analysis 16 revealed that the addition of a large amount of barium elongated an axis ͑b-axis for Pmnb symme-try͒, while the others were not altered. When considering four major peaks located in the range 30.5-32°, such as ͑121͒, ͑022͒, ͑200͒, and ͑103͒ peaks, the effect of a large amount of barium, namely, the peak shift toward the small angle side, was only detected for the ͑121͒ and ͑022͒ peaks, while the ͑200͒ and ͑103͒ peaks coincided exactly with the standard data of non-barium-doped and small amounts of barium-doped samples, as shown in Fig.…”
Section: Resultsmentioning
confidence: 91%